2021
DOI: 10.1007/s00572-020-01019-w
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical spatial sampling reveals factors influencing arbuscular mycorrhizal fungus diversity in Côte d’Ivoire cocoa plantations

Abstract: While many molecular studies have documented arbuscular mycorrhizal fungi (AMF) communities in temperate ecosystems, very few studies exist in which molecular techniques have been used to study tropical AMF communities. Understanding the composition of AMF communities in tropical areas gains special relevance as crop productivity in typically low fertility tropical soils can be improved with the use of AMF. We used a hierarchical sampling approach in which we sampled soil from cocoa (Theobroma cacao L.) planta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Furthermore, we found more indicator genera in the strongly acidic soils. Many previous studies have reported soil acidity to influence AMF community composition (Lekberg et al 2008;Dumbrell et al 2010;Bainard et al 2014;Rincón et al 2021), supporting the view that different AMF genera exhibited different sensitivities to soil pH. The reason for this is likely connected with the major role of soil pH in changing the physiological status of AMF, affecting sporulation (Wang et al 1993;Guo et al 1996) and growth of hyphae (Seguel et al 2013).…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, we found more indicator genera in the strongly acidic soils. Many previous studies have reported soil acidity to influence AMF community composition (Lekberg et al 2008;Dumbrell et al 2010;Bainard et al 2014;Rincón et al 2021), supporting the view that different AMF genera exhibited different sensitivities to soil pH. The reason for this is likely connected with the major role of soil pH in changing the physiological status of AMF, affecting sporulation (Wang et al 1993;Guo et al 1996) and growth of hyphae (Seguel et al 2013).…”
Section: Discussionmentioning
confidence: 75%
“…Even though the symbiotic nature and underground lifestyle of AMF could hinder efficient dispersal, attempts to determine the global distribution of AMF taxa have revealed that most of them are found in multiple continents (Davison et al, 2015; Savary et al, 2018). However, local environmental conditions and the spatial distance between sites are also important drivers of AMF community structure (Rincón et al, 2021). In line with this, Hazard et al (2013) demonstrated that landscape‐scale distribution of AMF taxa is driven by the local environment, especially by abiotic factors including pH, rainfall and soil type (Hazard et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, VTX00069, the closest match in the MaarjAM database (Öpik et al 2010) to our most abundant OTU, has been found in a tropical forest in Panama (Husband et al 2002), savannah in Madagascar (Yamato et al 2009), agricultural land in subtropical Mexico (Alguacil et al 2008), a tropical mountain rainforest in Ecuador (Kottke et al 2008), and a tropical forest in French Polynesia (Davison et al 2018). The second most abundant OTU could not be matched with a virtual taxon in the MaarjAM database, but did match with a sequence in the GlobalAMFungi database (Větrovský et al 2023), which came from a cocoa plantation in Côte d’Ivoire (Rincón et al 2021). Also our third most abundant OTU matched with a virtual taxon from the MaarjAM database (VTX00132) and could be traced back to many of the aforementioned studies in (sub)tropical regions (Husband et al 2002; Yamato et al 2009; Davison et al 2018), although it has also been observed in several studies in temperate or Mediterranean regions (de Leon et al 2016; Davison et al 2018).…”
Section: Discussionmentioning
confidence: 99%